2013
DOI: 10.1037/a0028228
|View full text |Cite
|
Sign up to set email alerts
|

Is working memory training effective? A meta-analytic review.

Abstract: It has been suggested that working memory training programs are effective both as treatments for attention-deficit/hyperactivity disorder (ADHD) and other cognitive disorders in children and as a tool to improve cognitive ability and scholastic attainment in typically developing children and adults. However, effects across studies appear to be variable, and a systematic meta-analytic review was undertaken. To be included in the review, studies had to be randomized controlled trials or quasi-experiments without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

96
1,138
13
35

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,543 publications
(1,308 citation statements)
references
References 103 publications
96
1,138
13
35
Order By: Relevance
“…Can fluid cognitive abilities such as working memory (WM) and reasoning be improved through computer-based WM training? This is a highly controversial question, with prior empirical studies (for reviews, see Morrison & Chein, 2011;von Bastian & Oberauer, 2014) and meta-analyses (Au et al, in press;Karbach & Verhaeghen, 2014;Lampit, Hallock, & Valenzuela, 2014;Melby-Lervåg & Hulme, 2013) providing contradictory findings. Although multiple previous studies revealed promising effects (e.g., Jaeggi, Buschkuehl, Jonides, & Perrig, 2008;Jaeggi, Buschkuehl, Shah, & Jonides, 2014;Jaeggi et al, 2010; Klingberg et al, 2005;Schweizer, Hampshire, & Dalgleish, 2011;Stepankova et al, 2014;, a growing number of other WM training interventions failed to induce such broad transfer (e.g., Chein & Morrison, 2010;Chooi & Thompson, 2012;Colom et al, 2013;Harrison et al, 2013;Redick et al, 2013;Salminen, Strobach, & Schubert, 2012; Sprenger et al, 2013;Thompson et al, 2013;von Bastian, Langer, Jäncke, & Oberauer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Can fluid cognitive abilities such as working memory (WM) and reasoning be improved through computer-based WM training? This is a highly controversial question, with prior empirical studies (for reviews, see Morrison & Chein, 2011;von Bastian & Oberauer, 2014) and meta-analyses (Au et al, in press;Karbach & Verhaeghen, 2014;Lampit, Hallock, & Valenzuela, 2014;Melby-Lervåg & Hulme, 2013) providing contradictory findings. Although multiple previous studies revealed promising effects (e.g., Jaeggi, Buschkuehl, Jonides, & Perrig, 2008;Jaeggi, Buschkuehl, Shah, & Jonides, 2014;Jaeggi et al, 2010; Klingberg et al, 2005;Schweizer, Hampshire, & Dalgleish, 2011;Stepankova et al, 2014;, a growing number of other WM training interventions failed to induce such broad transfer (e.g., Chein & Morrison, 2010;Chooi & Thompson, 2012;Colom et al, 2013;Harrison et al, 2013;Redick et al, 2013;Salminen, Strobach, & Schubert, 2012; Sprenger et al, 2013;Thompson et al, 2013;von Bastian, Langer, Jäncke, & Oberauer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Further limitations of the previous studies include too homogeneous groups and lack of measures of functional impairment (Chacko et al 2013;Rapport et al 2013). Thus, as briefly described above, and as concluded by several recent reviews and meta-analyses (Cortese et al 2015;Melby-Lervåg and Hulme 2013;Rapport et al 2013), not enough evidence were accumulated to support the efficacy of cognitive training in ADHD. In particular, the existing studies do not support the claim that the outcomes of cognitive training in general and of working memory training in particular, are transferable to other cognitive domains and/or to everyday functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Extant research has demonstrated support for the efficacy of cognitive training programs in improving individual cognitive skills (Holmes, Gathercole, & Dunning, 2009; Klingberg et al, 2005; Melby‐Lervag & Hulme, 2013; Sonuga‐Barke et al, 2013; Wegrzyn, Hearrington, Martin, & Randolph, 2012). However, because each training program described in the literature targets different cognitive skills, the results are as diverse and varied as the programs themselves.…”
mentioning
confidence: 99%